IMPLEMENTASI KEBIJAKAN DANA DESA BAGI PEMBANGUNAN KESEHATAN DI KABUPATEN DONGGALA - J e n i, J e n i (Katalogis, 2019)
Bert Objectiveof this studyto analyze the Implementation Of the Village Funds Policy forHealth Development in Donggala District.The theory used as the basis of analysis is the theory analysis of van Metter and Van Horn policy, consisting of sixaspects of basic measuresand policy objectives, policy resources, characteristics the executing agency, implementor's disposition, disposition between the organization and activities of the implementing and social, political and economic conditions. Qualitative methodscase study approach in three villages premises with depth interviews with 10 informant. Analysis of the data used is the Miles and Hubberman Models. The results showed that the implementation of the Village Fund Policy for Health Development In Donggala District was not well implemented. This can be seen from the six aspects studied, there are still aspects that have not yet been achieved, namely the Basic Measures and Policy Objectives, Policy Sources, characteristics of Implementing Agents have not fully supported, as well as the Conditions of Social research Environment, Politics and Economics. While the aspects that have been implemented are aspects of Implementor Disposition, and Inter-Organization Communication and Implementing Activities.